(untitled) (Al-Qamar, 2019)
This article studies thematic study of the Qur’anic concept of fear. It argues that thoughts and deeds which express the state of fear and they conceive the idea of ​​nurturing belief in the veins of man and this is what causes the concept of divinity, divinity and divinity to be refined in man, in solitude. The concept of responsibility emerges when the love of God Almighty prevails and acknowledges. Self-deception becomes a means of protection and self-accountability. The goals fulfill the Sharīʻah and the manifestations of fear and the manifestations of fear revealed the facts by which humanity in general and the Muslims in particular, by practicing, can achieve their worldly and otherworldly and eternal success and salvation.